Life history of abyssal and hadal fishes from otolith growth zones and oxygen isotopic compositions. (February 2018) - Gerringer, M.E.; Andrews, A.H.; Huss, G.R.; Nagashima, K.; Popp, B.N.; Linley, T.D.; Gallo, N.D.; Clark, M.R.; Jamieson, A.J.; Drazen, J.C.
Abstract: Hadal trenches are isolated habitats that cover the greatest ocean depths (6, 500–11, 000 m) and are believed to host high levels of endemism across multiple taxa. A group of apparent hadal endemics is within the snailfishes (Liparidae), found in at least five geographically separated trenches. Little is known about their biology, let alone the reasons for their success at hadal depths around the world. This study investigated the life history of hadal liparids using sagittal otoliths of two species from the Kermadec ( Notoliparis kermadecensis ) and Mariana ( Pseudoliparis swirei ) trenches in comparison to successful abyssal macrourids found at the abyssal-hadal transition zone. Otoliths for each species revealed alternating opaque and translucent growth zones that could be quantified in medial sections. Assuming these annuli represent annual growth, ages were estimated for the two hadal liparid species to be from five to 16 years old. These estimates were compared to the shallower-living snailfish Careproctus melanurus, which were older than described in previous studies, expanding the potential maximum age for the liparid family to near 25 years. Age estimates for abyssal macrourids ranged from eight to 29 years for Coryphaenoides armatus and six to 16 years for C. yaquinae . In addition, 18 O/ 16 O ratios (δ 18 O) were measured across the otolith using secondary ion mass spectrometry (SIMS) to investigate the thermal history of the three liparids, and two macrourids. Changes in δ 18 O values were observed across the otoliths of C. melanurus, C. armatus, and both hadal liparids, the latter of which may represent a change of >5 °C in habitat temperature through ontogeny. The results would indicate there is a pelagic larval stage for the hadal liparids that rises to a depth above 1000 m, followed by a return to the hadal environment as these liparids grow. This result was unexpected for the hadal liparids given their isolated environment and large eggs, and the biological implications and plausibility of interpretations of these data are discussed. This study presents a first look at the life history of some of the deepest-living fishes through otolith analyses. Highlights: First age estimation of hadal snailfishes from two trenches. Thermal history reconstruction from δ 18 O values for five deep-sea fishes. Evidence for possible pelagic larval stage above the thermocline for hadal liparids. An increase to the possible maximum age for the family Liparidae in Careproctus melanurus . Age estimates for two abyssal species, Coryphaenoides armatus and C. yaquinae .